Tolerance for Wolves in the United States - Slagle, Kristina M.; Wilson, Robyn S.; Bruskotter, Jeremy T. (Frontiers in Ecology and Evolution, 2022)
This study applies a psychological hazard-acceptance model to U.S. wolf conservation. Where most prior studies have focused on human populations most likely to interact with wolves (e.g., people who reside in wolves’ range), we sought to model tolerance among the general public throughout the United States, with representative samples from two regions with ongoing recovery efforts (i.e., the Northern Rocky Mountains and Western Great Lakes) as well as the rest of the country. As opposed to typical, attitudinal measures of tolerance (e.g., wildlife acceptance capacity) we sought to model supportive and oppositional behavior among the U.S. public as a function of perceptions of risk, benefit, and control, trust in the U.S. Fish and Wildlife Service, and affect toward wolves. At the national level, results predict a moderate amount of the variance for tolerant, stewardship behaviors (r2 = .22-.25) and intolerant, oppositional behaviors to wolf conservation (r2 = .14-.22). Most respondents (55%) did not intend to engage in either supportive or oppositional actions, and 23% indicated a preference for wolf populations to increase nationally. These preferences varied slightly by sample region when weighted to reflect regional demographics, with about one in three respondents in the Northern Rocky Mountains preferring for wolf populations to increase (32%), and slightly fewer saying the same in the Western Great Lakes region (30%) and rest of the U.S. (27%). We performed a post-hoc logistic regression to identify factors that predisposed U.S. residents nationally to engage in any behavior towards wolves (tolerant or intolerant). This analysis suggested that the perceived importance of the wolf issue was most predictive of intentions to engage in behavior relevant to wolf conservation. Analyses indicate high levels of tolerance for wolves nationally, some support for their restoration, and only small minorities engaging in oppositional behavior. With the recent shift to individual state-level management, a more diverse policy matrix will increase the importance of understanding how human tolerance for wolves varies spatially (at the local level), and what factors drive tolerance at both the individual and group level.